2020
DOI: 10.1016/j.ophtha.2020.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Increased Time Outdoors Is Followed by Reversal of the Long-Term Trend to Reduced Visual Acuity in Taiwan Primary School Students

Abstract: Purpose: To investigate the change in the prevalence of reduced visual acuity (VA) in Taiwanese school children after a policy intervention promoting increased time outdoors.Design: Prospective cohort study based on the Taiwan School Student Visual Acuity Screen (TSVAS) by the Ministry of Education in Taiwan.Participants: All school children from grades 1 through 6 were enrolled in the TSVAS from 2001 through 2015.Methods: The TSVAS requires each school in Taiwan to perform measurements of uncorrected VA (UCVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 17 publications
3
61
0
Order By: Relevance
“…Studies both in Finland (Pärssinen 1986) and Singapore (Dirani et al 2009) along with several other studies (Rose et al 2008; He et al 2015; Guo et al 2017; Huang et al 2019; Wu et al 2020) have found that individuals who spent more time outdoors were less likely to be myopic. In the present study, the considerable differences between the Singaporean and Finnish children in time spent outdoors did not explain the differences between the two populations in myopic progression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies both in Finland (Pärssinen 1986) and Singapore (Dirani et al 2009) along with several other studies (Rose et al 2008; He et al 2015; Guo et al 2017; Huang et al 2019; Wu et al 2020) have found that individuals who spent more time outdoors were less likely to be myopic. In the present study, the considerable differences between the Singaporean and Finnish children in time spent outdoors did not explain the differences between the two populations in myopic progression.…”
Section: Discussionmentioning
confidence: 95%
“…About 70% of the children in both the SCORM groups spent ≤0.5 h/d outdoors and only about 10% ≥1 h/d, whereas more than 70% of the Finnish children, but only about 1% of the Singaporean children, spent ≥2 h/d outdoors. In a prospective cohort study started in 2010 among schoolchildren in Taiwan, recommendations were 2 h/d outdoor time and a break of 10 min after every 30 min of near‐work (Wu et al 2020). During the follow‐up, the trend towards an increase in poor uncorrected distant vision significantly reversed (Wu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of more outdoor time was further confirmed in an RCT in Taiwan 13 . The same investigators in Taiwan reported that the prevalence of myopia was reduced from 49.4% in 2012 to 46.1% in 2015, when an outdoor time intervention programme was implemented 73 . The association between outdoor light exposure and myopia has been further supported by some observational studies on seasonal variation and myopia development, which found that myopia progression and eye growth were slower in the summer 74 .…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…Nevertheless, a campaign conducted in Taiwan to educate parents about the benefits of spending time outdoors outside of school time and an incentive-based outdoor programme with family did not have a significant effect on increasing outdoor time 12,188 . Of note, a 15-year study in Taiwan (the Tian-Tian 120 programme) encouraged schools to allow students to spend 2 hours outdoors daily and demonstrated a reversal in the long-term trend of increased prevalence of reduced visual acuity (which has a high correlation with myopia) in schoolchildren 73 . This finding shows that a school policy for increasing outdoor time might be a direct and effective way of maintaining visual acuity.…”
Section: Preventionmentioning
confidence: 99%
“… A unique situation may not have been considered yet. Taiwan is one of the countries which has a very high rate of myopia, e.g., around 84% of high school students [ 22 ], and the group with presbyopia means roughly 40 to 50% of all citizens wear glasses. The combination of eyewear, medical masks, and frequent hygiene might play a synergistic role in preventing the spread of COVID-19.…”
Section: Limitations and Other Assumptionsmentioning
confidence: 99%